Inhalation Aromatherapy via Brain-Targeted Nasal Delivery: Natural Volatiles or Essential Oils on Mood Disorders - Cui, Jieqiong; Li, Meng; Wei, Yuanyuan; Li, Huayan; He, Xiying; Yang, Qi; Li, Zhengkun; Duan, Jinfeng; Wu, Zhao; Chen, Qian; Chen, Bojun; Li, Gang; et al. (Frontiers in Pharmacology, 2022)
Mood disorders, also often referred to as affective disorders, are a group of psychiatric illnesses that severely impact mood and its related functions. The high medical expenditures have placed a significant financial burden on patients and their families. Aromatherapy is an alternative and complementary treatment that utilizes essential oils (EOs) or volatile oils (VOs) to achieve major therapeutic goals. In general, EOs are volatile chemicals that enter the body primarily through skin absorption and/or nasal inhalation. In addition, they can work through oral administration. Inhalation aromatherapy has shown unique advantages for treating mood disorders, especially depression, anxiety and mental disorders such as sleep disorder, which have been validated over the last decade through clinical and preclinical studies. Accumulating evidence has shown that EOs or VOs can bypass the blood-brain barrier to target brain tissue through the nasal-brain pathway. Subsequently, they act on the cerebral cortex, thalamus, and limbic system in the brain to improve symptoms of anxiety, depression and improve sleep quality. Here, we review the natural aromatic plants' volatiles or essential oils used commonly as adjuncts to manage mood disorders and illustrate the mechanisms of inhalation aromatherapy. Mainly summarized the application of transnasal inhalation aromatherapy in depression, anxiety, and sleep disorders. We conclude that aromatherapy does not cause side-effects, which is vastly different from commonly used psychotropic drugs. Inhalation aromatherapy via brain-targeted nasal delivery offers potentially efficacious treatment for mental disorders and merits further study.